Analisis Hak Tenaga Kerja Perempuan Pt. Freeport Indonesia dalam Mendukung Kesetaraan Gender Terhadap Perempuan Berdasarkan Goals ke-5 SDGS Tahun 2017-2019 - Marsel, Bergitha Yesika; Cornelis, Roberto Octavianus; Hergianasari, Putri; Hergianasari, Putri (Jurnal Ilmiah Widya Sosiopolitika; Vol 5 No 2 (2023): DIPLOMASI DAN ISU-ISU INTERNASIONALDO - 10.24843/JIWSP.2023.v05.i02.p02, 2023)
Gender equality is a concept based on human rights. This concept sees that in social phenomena, the position of women in aspects of work, particularly in the mining sector tends to give rise to a negative perspective. For this reason, it is necessary to have international actors, both individuals and groups, and countries to be able to encourage gender mainstreaming which is supported by the 5th SDGs. This study analyzes the position of women in the mining sector at PT. Freeport Indonesia, whether the empowerment of female workers has fulfilled labor rights, and whether there are regulations in creating gender equality in the company environment in 2017-2019. This study uses a descriptive qualitative method that looks at the cause-and-effect relationships of the social phenomena that occur. The final result of this paper leads to a liberal feminist view that women have opportunities in the economic aspect, and obtain the same rights as men in managing existing resources. This is in accordance with the gender equality approach in the 5th SDGs with the fulfillment of global targets for women's empowerment by PT. Free port Indonesia.